The Effect of Sharia Financial Literacy on the Interest in Becoming a Customer at KB Bank Syariah Bukopin Darmo Branch Office - Farida Fatmawati; Dwi Salma Nabila; Anis Fitriyanti; Yunita Nur Hidayatus (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the influence of Islamic financial literacy on public interest in becoming customers of KB Bank Syariah Bukopin, Darmo Branch. The research was motivated by the low public understanding of Islamic banking products and principles. Using a qualitative case study approach, data were collected through semi-structured interviews, participatory observation, and document analysis. The findings reveal three main themes: (1) understanding Islamic finance concepts enhances confidence in bank products, (2) religiosity-based trust increases transactional security, and (3) service and educational experiences strengthen customer interest. Analysis using the Miles and Huberman interactive model indicates that Islamic financial literacy serves both cognitive and affective roles in influencing customer interest, supported by effective communication and service strategies. The study concludes that Islamic financial literacy not only improves public understanding but also reinforces their intention to choose Islamic banking. Theoretically, this study expands the perspective on Islamic financial literacy by highlighting experiential and value-based dimensions. Practically, it provides insights for Islamic banks, particularly KB Bukopin Syariah, to design more effective educational and marketing strategies. Future research should integrate qualitative and quantitative methods for broader validation.